Superfluids and Superconductors - Zivieri, Roberto (IntechOpen, 2018)
This book covers some of the most recent advances in the field of superfluids and superconductors. More specifically, it presents some of the most advanced theoretical formulations of superfluidity and superconductivity with special regard to their topological properties and vortex dynamics together with a description of the main experiments carried out via experimental techniques at the forefront to study these two such important phenomena in condensed matter physics. Special emphasis is given to ultracold Fermi gases, to clean liquid helium and to vortex membranes and knots for the class of superfluids and to the emerging superconductivity, to intermediate states in type-I superconductors, and to heat treatments to modulate the critical temperature for the class of superconductors.